Fatal fulminant hepatitis associated with Ganoderma lucidum (Lingzhi) mushroom powder - Harirak Wanmuang (2018)
Hepatotoxic effect related to Ganoderma lucidum (Lingzhi) mushroom powder was first described in a patient from Hong Kong in 2004. In 2005, the authors experienced a case of fatal fulminant hepatitis associated with such a preparation. Both patients had taken other therapeutic agents and traditionally boiled Lingzhi without any toxic effect. After switching to taking Lingzhi in powder form for 1-2 months, the hepatotoxic episode occurred in both patients. The toxic role of Lingzhi powder needs close monitoring in the future, especially in combination with other drugs.